Identification of the Degradation Products from α‐Ionone Used as Stabiliser in "Green" Propellants through its Lifetime. Issue 11 (24th September 2021) - Damseaux, Caroline; Scholl, Georges; Damblon, Christian; Dejeaifve, Alain; Dobson, Rowan; Ma, Xiaofeng; Marko, Istvan; Monbaliu, Jean‐Christophe M.; De Pauw, Edwin; Eppe, Gauthier
Abstract: A stabiliser is added to gun and rocket propellants to react with species responsible for degradation during decomposition. Propellant powder manufacturers and army personnel are confronted with toxicity during powder degradation and must replace current stabilisers with non‐toxic molecules. According to the STANAG 4582 (North Atlantic Treaty Organization (NATO) Standardisation Agreement [1]), propellant powders must remain chemically stable for a minimum of ten years when stored at temperatures equivalent to an isothermal storage (25 °C). Single and double base smokeless powders with α‐ionone as a "green" stabiliser are tested and the results show that the heat flow is stable over time and that the autocatalysis occurs 2 to 3 times later than in powders with conventional stabilisers. This stabiliser is efficient for all nitrate ester‐based propellants. In the present paper, we identify and monitor the evolution of the main degradation products over time by nuclear magnetic resonance (NMR), mass spectrometry (MS) to unravel the stabilisation mechanism under accelerated aging conditions. A time‐related fluctuation of their respective amounts (increasing then decreasing, then re‐increasing, …) is observed, which indicates that the daughter products have also a stabilisation effect. The three major α‐ionone daughter products are identified as: 3‐oxo‐α‐ionone, 4‐oxo‐β‐ionone and 4, 5‐epoxy‐α‐ionone. Abstract :